EFFECT OF POULTRY MANURE LEVELS ON THE PRODUCTIVITY OF SPRING MAIZE (Zea mays L.). - W. Farhad; M. F. Saleem; M. A. Cheema; H. M. Hammad (Journal of Animal and Plant Sciences, 2009)
Poultry manure has long been recognized the most desirable organic fertilizer. It improves soil fertility by adding both major and essential nutrients as well as soil organic matter which improve moisture and nutrient retention. The present paper investigates the effectiveness of different levels of applied poultry manure (PM) on the growth and yield of spring maize (Zea mays L). Research was carried out at the Agronomic Research Area, University of Agriculture, Faisalabad during spring season 2007. The experiment consisted of six treatments: control, 4 t ha-1 PM, 6 t ha-1 PM, 8 t ha-1 PM, 10 t ha-1 PM and 12 t ha-1 PM. Experiment was laid out in randomized complete block design with three replications. Number of cobs per plant was affected non significantly by the application of different levels of PM. While all others recorded parameters including plant height, number of rows per cob, number of grains per row, 1000-grain weight, grain yield, biological yield and harvest index were significantly affected by application of PM. Maximum values for all these parameters were recorded with the application of 12 t ha-1 PM.
Keywords: Maize (Zea mays L.); poultry manure; growth; yield